Ice nucleation properties of rust and bunt fungal spores and their transport to high altitudes, where they can cause heterogeneous freezing. Issue 13 (8th July 2013) - Haga, D. I.; Iannone, R.; Wheeler, M. J.; Mason, R.; Polishchuk, E. A.; Fetch, T.; van der Kamp, B. J.; McKendry, I. G.; Bertram, A. K.
Abstract : [1] Rust and bunt spores that act as ice nuclei (IN) could change the formation characteristics and properties of ice‐containing clouds. In addition, ice nucleation on rust and bunt spores, followed by precipitation, may be an important removal mechanism of these spores from the atmosphere. Using an optical microscope, we studied the ice nucleation properties of spores from four rust species ( Puccinia graminis, Puccinia triticina, Puccinia allii, and Endocronartium harknesssii ) and two bunt species ( Tilletia laevis and Tilletia tritici ) immersed in water droplets. We show that the cumulative number of IN per spore is 5 × 10 −3, 0.01, and 0.10 at temperatures of roughly −24°C, −25°C, and −28°C, respectively. Using a particle dispersion model, we also investigated if these rust and bunt spores will reach high altitudes in the atmosphere where they can cause heterogeneous freezing. Simulations suggest that after 3 days and during periods of high spore production, between 6 and 9% of 15 µm particles released over agricultural regions in Kansas (U.S.), North Dakota (U.S.), Saskatchewan (Canada), and Manitoba (Canada) can reach at least 6 km in altitude. An altitude of 6 km corresponds to a temperature of roughly −25°C for the sites chosen. The combined results suggest that (a) ice nucleation by these fungal spores could play a role in the removal of these particles from the atmosphere and (b) ice nucleation by these rust and bunt spores are unlikely to compete with mineral dust on a global and annual scale at an altitude of approximately 6 km. Key Points: Rust and bunt spores act as heterogeneous ice nuclei